The effects of exercise intensity on energy expenditure, weight, and lee's index in adolescent obese rats - Li, Qiang; Jones, Chloe (Cambridge Sport Science, 2025)
Objective: To investigate the effects of different intensity exercise prescriptions on immediate energy expenditure, body weight, and Lee's Index in adolescent obese rats immediately after exercise during an 8-week weight loss process. Methods: After 7 weeks of modeling, 32 obese rats were randomly divided into 4 groups, with 8 rats in each group: obese control group, low-intensity exercise group, moderate-intensity exercise group, and high-intensity exercise group. The running speeds on the treadmill for the three intensity levels were set at 15–18 m/min, 21–25 m/min, and 28–32 m/min, respectively, with 5 sessions per week and 60 minutes per session for 8 weeks. Body weight was measured and Lee's Index was calculated weekly. A rat metabolic system was used to measure the immediate oxygen uptake and energy expenditure in rats after exercise. Results: During the 8-week intervention, the exercise groups showed significantly higher immediate post-exercise muscle oxygen uptake and total oxygen uptake, as well as muscle energy expenditure and total energy expenditure compared to the control group (P<0.05, P<0.01). The high-intensity group had higher values than the low-intensity group (P<0.05). Weight gain was significantly lower in the intervention groups compared to the control group (P<0.05, P<0.01). Lee's Index was significantly lower in the intervention groups at week 8 compared to the control group (P<0.05, P<0.01), with no significant differences between different exercise intensities (P>0.05). In adolescent obese rats, body weight tends to increase with age, while muscle oxygen uptake, total oxygen uptake, muscle energy expenditure, and total energy expenditure tend to decrease. After 8 weeks of exercise intervention, different intensity exercise prescriptions can increase immediate post-exercise oxygen uptake and energy expenditure in adolescent obese rats, with the most significant effects observed in the high-intensity group. Weight gain and Lee's Index were reduced, but the effects were less influenced by exercise intensity.